Liryczność brulionowa Zygmunta Krasińskiego w kontekście wiersza "Bóg mi odmówił tej anielskiej miary" - Szczeglacka-Pawłowska, Ewa (Colloquia Litteraria, 2012)
Zygmunt Krasiński’s Notebook Lyricism in the context of the poem entitled Bóg mi odmówił tej anielskiej miary The article is an interpretation of Krasiński’s poem with respect to ‘notebook romanticism’ category. The author analyses the poem in the light of Krasiński’s literary creation process, which is preserved in the Romantic art of editing.